Sosialisasi Undang-Undang Nomor 32 Tahun 2004 Tentang Pemerintahan Daerah Di Kelurahan Hamdan Kecamatan Medan Maimun Kota Medan - Walid Mustafa Sembiring; Evi Yunita Kurniaty; Yurial Arief Lubis; Bahrum Jamil; Agung Suharyanto (Pelita Masyarakat, 2021)
Community service is one of the activities aimed at assisting the government in society and local governments in disseminating Law no. 32 of 2004 concerning Local Government in Hamdan Village, Medan Maimun District, Medan City. The lack of understanding of the people of Hamdan Village, Medan Maimun District in the success of Law No. 32 of 2004. The results of this dedication show that the socialization of Law Number 32 of 2004 concerning Regional Government and development progress and the success of existing development, must be disseminated to the community. One example of the community can directly experience the construction of road facilities and infrastructure that have repaired, as well as several developments in flood management and environmental cleanliness. The participation of the community in determining public policy, the higher the level of democracy in the country. In regional autonomy it is necessary to involve as many citizens as possible in determining public policy at the regional level.